Panel zone behavior of diaphragm-through connection between concrete-filled steel tubular columns and steel beams. Issue 4 (April 2016) - Wu, Liao; Chen, Zhihua; Rong, Bin; Luo, Song
The diaphragm-through connections are some of the most widespread connections between concrete-filled steel tubular columns and steel beams. In this work, five tee-shaped diaphragm-through connections were fabricated so that they comply with the principle of "strong members and weak panel zone." Low-frequency cyclic loading was applied to the specimens to investigate the panel zone behavior of the connections. Based on the test results, the force transfer mechanism and the effect of different factors on the panel zone shear capacity were analyzed. In addition, different methods of calculating the panel zone shear strength were compared with the experimental data. The results show that the shear capacity of the panel zone of the connection is borne mainly by the steel tube webs and the core concrete. The steel frame composite with steel tube flanges and diaphragms strengthens the plastic deformation ability after yielding. It was found that in the existing computational methods for panel zone shear capacity of the connection, the calculated results are in agreement with the test results for the shear capacity of the steel tube webs, but the predicted values are not consistent with the concrete component capacity.